The Mediating Role Of Investment Motivation In The Relationship Between Risk Perception And Financial Literacy On Investment Decisions Of Paylater Users - Yuliyanti, Eka; Turmudhi, Anis; Kartika, Andi; Mustahidda, Rahmania; Fadhila, Zati Rizka (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study examines the mediating role of investment motivation in the relationship between risk perception, financial literacy, and investment decisions among PayLater users in Indonesia. Utilizing a quantitative explanatory approach, data were collected from 200 respondents aged 18–45 who had used PayLater services for more than six months. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze both direct and indirect effects between constructs. The findings reveal that risk perception and financial literacy positively influence investment motivation. Investment motivation, in turn, has a significant positive effect on investment decisions and serves as a strong mediator between risk perception, financial literacy, and investment decisions. Although financial literacy only marginally affects investment decisions directly, its indirect effect through motivation is significant. The results emphasize the importance of enhancing both financial literacy and investment motivation to improve the quality of investment decisions in the context of digital financial services like PayLater.